Optimalisasi Alternatif Pembiayaan Infrastruktur Transportasi dengan Meningkatkan Kompetensi Sumber Daya Manusia - Sugihardjo Sugihardjo (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2022)
ABSTRACTOptimizing the Alternative of Transportation Infrastructure Financing by Improving Human Resource Competence: The development of transportation infrastructure is one of Indonesia's programs to support the country's economic development. In the Strategic Plan of the Ministry of Transportation for 2020-2024, a total transportation infrastructure investment of Rp. 1288 t is required, of which the Ministry of Transportation's APBN can only meet 20% (Rp 266.64 T) of the total investment requirement. A financing scheme is needed to meet the gap in infrastructure investment needs and the fiscal capacity of the State Revenue and Expenditure Budget (APBN) for transportation infrastructure development. This study aims to analyze the most optimal financing alternatives for transportation infrastructure in Indonesia. Data collection in this study was carried out using document review, literature review, and interview methods with stakeholders. Analysis was carried out using descriptive comparative analysis and Analytic Hierarchy Process (AHP). Based on the results of descriptive comparative analysis, it is known that business entities can contribute to infrastructure development if the Internal Rate Return (IRR) is greater than 10%. As well as the results of AHP's financial analysis, it was found that the feasibility factor has the highest priority. The result shows two main indicators for infrastructure financing that affect the level of business entity investment, namely financial feasibility and risk allocation between business entities and the government. These two results describe the need for Human Resource competence in supporting the optimization of infrastructure financing alternatives.Keywords: Infrastructure investment, Creative Financing, and Human Resource Development.ABSTRAKPembangunan infrastruktur transportasi merupakan salah satu program yang direncanakan di Indonesia untuk mendukung perkembangan ekonomi suatu negara. Dalam Rencana Strategis Kementerian Perhubungan Tahun 2020-2024, dibutuhkan total investasi infrastruktur transportasi sebesar Rp1.288 triliun, dimana APBN Kementerian Perhubungan hanya mampu memenuhi sebesar 20% (Rp266,64 triliun) dari total kebutuhan investasi. Untuk mengoptimalkan pengembangan infrastruktur transportasi dibutuhkan skema pembiayaan untuk memenuhi gap kebutuhan investasi infrastruktur dan kemampuan fiskal Anggaran Pendapatan dan Belanja Negara (APBN). Penelitian ini bertujuan untuk mengoptimalkan alternatif pembiayaan dalam investasi infrastruktur transportasi di Indonesia. Pengumpulan data pada penelitian ini dilaksanakan dengan metode review dokumen, literatur dan wawancara kepada beberapa stakeholders. Analisis dilakukukan dengan 2 (dua) metode yaitu dengan menggunakan komparatif deskriptif dan Analytic Hierarchy Process (AHP). Berdasarkan hasil analisis komparatif deskriptif, ditemukenali bahwa badan usaha dapat berkontribusi di dalam pengembangan infrastruktur jika Internal Rate Return (IRR)>10%. Serta hasil analisa AHP diperoleh bahwa faktor kelayakan finansial memiliki urutan prioritas pertama. Hal ini menunjukkan pembiayaan infrastruktur terdapat 2 (dua) indikator utama yang mempengaruhi tingkat investasi badan usaha, yaitu kelayakan finansial serta alokasi risiko antara badan usaha dan pemerintah. Berdasarkan kedua hasil analisis tersebut, dapat dijabarkan kebutuhan kompetensi SDM dalam mendukung optimalisasi alternatif pembiayaan infrastruktur.Kata Kunci: Investasi Infrastruktur, Creative Financing, Sumber Daya Manusia